2022
DOI: 10.3384/njvet.2242-458x.2212347
|View full text |Cite
|
Sign up to set email alerts
|

How can students in vocational education be motivated to learn mathematics?

Abstract: The aim of this article is to discuss how mathematics teaching with a closer connection to students’ vocational orientation can increase their motivation to learn mathematics. This article uses a motivation theory called self-determination theory to analyse interviews and observations made in two different studies investigating mathematics in vocational education. The results indicate that there are many vocational students who are unmotivated to learn mathematics because they do not see any relevance in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Based on high school mathematics curriculum, the concept studied consisted of "Understanding the real number system, various types, including power numbers and their uses in various appropriate contexts." The participants also revealed that students must have the ability to carry out mental and rough calculations, as well as reasonable judgments [27]. Mathematics teachers referred to the word analyze as a connection to the essential concepts of mathematics in terms of systems of equations, mathematical modeling, linear programming, and probability, which were in the high school curriculum.…”
Section: Teachers' Understanding Of Mathematics In the Crop Agribusin...mentioning
confidence: 99%
“…Based on high school mathematics curriculum, the concept studied consisted of "Understanding the real number system, various types, including power numbers and their uses in various appropriate contexts." The participants also revealed that students must have the ability to carry out mental and rough calculations, as well as reasonable judgments [27]. Mathematics teachers referred to the word analyze as a connection to the essential concepts of mathematics in terms of systems of equations, mathematical modeling, linear programming, and probability, which were in the high school curriculum.…”
Section: Teachers' Understanding Of Mathematics In the Crop Agribusin...mentioning
confidence: 99%
“…I tillegg viser forskning at en laererstyrt undervisning, som kjennetegnes ved at laereren har klare mål og struktur i sitt arbeid, fremmer motivasjon, utholdenhet og gode laeringsstrategier (Kaplan, 2002;Karabenick, 2004;Midgeley & Urdan, 2001;Muhrman, 2022). Tydelige målformuleringer for opplaeringen og sammenheng mellom innhold og arbeidsmetoder er viktige forutsetninger for elevenes motivasjon.…”
Section: Motivasjon For Laeringunclassified
“…Metodene viser konkret hvordan laereren legger til rette for og leder laeringsarbeidet og hvilke aktiviteter elevene gjennomfører som skal sikre elevenes kunnskapsutvikling. Forskning viser blant annet at en laererstyrt og målrettet undervisning bidrar til både elevenes laeringsutbytte og motivasjon (Kaplan, 2002;Karabenick, 2004;Midgeley & Urdan, 2001;Muhrman, 2022).…”
Section: Undervisningsmetoderunclassified